(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The digital world has revolutionized communication, but it has also become a breeding ground for harmful behaviors like sexual harassment and cyberbullying. These issues pose serious threats to individuals' well-being and require a multifaceted approach to address them effectively. Sexual harassment in the digital realm can manifest in various forms, including unsolicited explicit images or messages, online stalking, and threats of sexual violence. The anonymity and accessibility of the internet can embolden perpetrators, while victims may feel isolated and powerless. Cyberbullying, on the other hand, involves the use of electronic communication to bully a person, typically by sending messages of an intimidating or threatening nature. It can include name-calling, spreading rumors, or excluding someone from online groups. The constant nature of online platforms can make it difficult for victims to escape the harassment, leading to significant emotional distress and even self-harm. The digital world has revolutionized communication, but it has also become a breeding ground for harmful behaviors like sexual harassment and cyberbullying. These issues pose serious threats to individuals' well-being and require a multifaceted approach to address them effectively.